Genetic Variability of Agronomic Traits as Potential Indicators of Drought Tolerance in Common Beans (Phaseolus vulgaris L.). (25th August 2019) - Langat, Charles; Ombori, Omwoyo; Leley, Philip; Karanja, David; Cheruiyot, Richard; Gathaara, Moses; Masila, Benard
Abstract : Sixteen progeny lines of common beans obtained from single crosses made between two parents, GLP2 and KAT B1, were grown in randomized complete block design in a rainout shelter at the Agricultural and Mechanization Research Institute, Machakos, Kenya. The experiment was conducted to study inheritance of traits associated with drought stress adaptation and to establish if significant variation for those traits was existing in order to carry out selection for drought tolerance. The calculated mean values were used to estimate heritability, genetic advance, and correlation study for each trait. Water stress had a significant (p ≤ 0.01 ) effect on the number of pods per plant, grains per plant, 100-seed weight, and yield per plant. The highest values for genotypic coefficient of variation (36.11%) and phenotypic coefficient of variation (36.70%) were recorded for pods plant -1 under stress condition. Highest broad-sense heritability estimates (96.54%, 94.97%, and 93.16%) coupled with high genetic advance as percent of the mean (22.32%, 34.97%, and 26.32%) were obtained for the number of pods plant −1, days to maturity, and yield plant −1, respectively, showing that selection of these traits together could lead to yield improvement under stressed conditions. Harvest index showed a significant and positive relationship with biomass aboveground (r = 0.86 ) and the number of pods plant −1 (r = 0.86 ) indicating the possibility of identifying high performing lines of common beans for drought stress environment for further studies on these traits.